The value of economic security of the Russian Federation in the era of globalization (Journal of Economic Research & Business Administration, 2019)
The article analyzes the problems of economic security. Economic security is the state of the national economy that provides for the satisfaction of the country’s vital needs for material goods, regardless of the occurrence of force majeure of a socio-political, economic or environmental nature in the global economic system or within the country. Ensuring economic security in the state, as well as any economic entityin Russia has a significant role, is implemented through the mechanism of economic security, whichacts as a system of measures to prevent economic threats (economic monitoring, forecasting, detectionand prevention of threats, the definition of limit (threshold) indicators). Economic security in the era ofglobalization is an important component of national security, as the economy permeates all spheres ofactivity of the state. The authors investigate the evolutionary trend of modern society in the era of globalization.In a single economic space globalization acts as a new level of economic activity. In the contextof globalization, despite the existing risks, challenges and threats to economic security, it is necessaryto take into account the factors of strengthening the national economy and increasing its competitiveness.The article analyzes the threats to the economic security of Russia. Today, the Russian economy isunder the pressure of sanctions, which poses a threat to its stabilization so ensuring economic security isone of the key conditions for its consolidation. In the state of economic security, sustainable economicgrowth is ensured, as well as the protection of the country’s economic interests at all levels: national andinternational. Threats to economic security are phenomena and processes that have a negative impact onthe economy of the country, infringing on the economic interests of the individual, society and the state.